2001
DOI: 10.1038/ng703
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the gene encoding immunoglobulin μ-binding protein 2 cause spinal muscular atrophy with respiratory distress type 1

Abstract: Classic spinal muscular atrophy (SMA) is caused by mutations in the telomeric copy of SMN1. Its product is involved in various cellular processes, including cytoplasmic assembly of spliceosomal small nuclear ribonucleoproteins, pre-mRNA processing and activation of transcription. Spinal muscular atrophy with respiratory distress (SMARD) is clinically and genetically distinct from SMA. Here we demonstrate that SMARD type 1 (SMARD1) results from mutations in the gene encoding immunoglobulin micro-binding protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
233
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(244 citation statements)
references
References 27 publications
2
233
0
4
Order By: Relevance
“…604320) of humans (23,24). However, the feline IGHMBP2 locus was excluded as the feline SMA gene by the same approach of intragenic marker development and linkage analysis demonstrated in this report (Q.H.…”
Section: Feline Spinal Muscular Atrophymentioning
confidence: 90%
“…604320) of humans (23,24). However, the feline IGHMBP2 locus was excluded as the feline SMA gene by the same approach of intragenic marker development and linkage analysis demonstrated in this report (Q.H.…”
Section: Feline Spinal Muscular Atrophymentioning
confidence: 90%
“…Intriguingly, senataxin itself is mutated in a juvenile-onset form of ALS, designated ALS4, that bears a striking resemblance to SMA and results in loss of motor neurons in early childhood (59). An additional RNA:DNA helicase, IGHMBP2, was initially characterized in the context of R-loop-dependent class-switch recombination, but it has since been found that loss-of-function mutations in IGHMBP2 cause spinal muscular atrophy type I with respiratory distress (60,61). These two independent lines of genetic evidence, in addition to our results, provide strong support for the causative role of unresolved R-loops in motor neuron disease.…”
Section: Discussionmentioning
confidence: 99%
“…A variant was considered to have musculoskeletal implications if (1) it is located within 100 kb or if it is an eQTL for a gene that has a relevant OMIM annotation, including association with human syndromes and animal models of relevant gene knock-outs, [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] such as abnormal skeletal, muscle, or cartilage development and abnormal body size or bone morphology, and (2) there are any skeletalrelated GWAS signals within 100 kb, such as bone mineral density. For example, rs35863206 (WEAF 22.35%, beta ¼ À0.0232, height p ¼ 5.91 3 10 À9 ) is a deletion located 53 kb upstream of PGR, which encodes the progesterone receptor protein and is correlated with rs147581469 (r 2 ¼ 0.72), a previously identified eQTL for PGR.…”
Section: Musculoskeletal Phenotypesmentioning
confidence: 99%